Biocompatibility of borosilicate glass‐ceramics based LTCC materials for microfluidic biosensor application. Issue 1 (26th August 2019) - Liang, Yongyuan; Ma, Mingsheng; Qian, Suxiang; Zhuang, Hui; Li, Kunqiang; Liu, Zhifu; Li, Yongxiang
Abstract: Three kinds of borosilicate glass‐ceramics Low temperature co‐fired ceramics (LTCC) substrate materials, Ca‐B‐Si‐O (CBS), Ca‐Al‐B‐Si‐O (CABS), and Ca‐Mg‐B‐Si‐O (CMBS), have been prepared, and the biocompatibility of these materials was evaluated. Compared with CBS and CMBS samples, the CABS sample presented the lowest crystallinity and dissolution in the bioleaching experiments. The direct and indirect cell culturing results showed that the CABS sample also possessed the best biocompatibility to the bone mesenchymal stem cells (BMSCs) due to its good bio‐stability and surface micro‐pore structure. The effects of surface topography and released ions on cytocompatibility were analyzed. These results were expected to offer some guideline information for developing LTCC substrate materials used in the microfluidic biosensors for the future biological and medical application.